2021
DOI: 10.3390/healthcare10010060
|View full text |Cite
|
Sign up to set email alerts
|

Does Internet Use Affect Medical Decisions among Older Adults in China? Evidence from CHARLS

Abstract: Background: The rapid growth of the elderly population poses a huge challenge for people to access medical services. The key to get rid of the dilemma is for patients to go firstly to primary medical institutions. Existing studies have identified numerous factors that can affect patients’ health institution choice. However, we currently know little about the role of Internet use in the patients’ medical decisions. The objective of this study is to explore health-seeking behavior and institution choice under th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(18 citation statements)
references
References 71 publications
(72 reference statements)
1
9
0
Order By: Relevance
“…Participants who used the internet to access information were more likely to choose general/specialized hospitals compared to participants without the internet to access information (P < 0.001), which indicated that the over ow of health information on the internet exacerbated the likelihood of going to higher-level healthcare institutions for seeking health treatment. Similarly, several previous studies were consistent with our nding [27,28].…”
Section: Discussionsupporting
confidence: 93%
“…Participants who used the internet to access information were more likely to choose general/specialized hospitals compared to participants without the internet to access information (P < 0.001), which indicated that the over ow of health information on the internet exacerbated the likelihood of going to higher-level healthcare institutions for seeking health treatment. Similarly, several previous studies were consistent with our nding [27,28].…”
Section: Discussionsupporting
confidence: 93%
“…In addition, internet use may have a greater impact on the middle-aged population than on the older adult population. It may be that middle-aged people are more receptive to and understanding of information and are therefore better able to use the internet to improve their health [ 77 ].…”
Section: Discussionmentioning
confidence: 99%
“…Patient choices and behaviors are driven by a number of factors [ 37 ], including hospital reputation, treatment quality, insurance plan, Internet equipment, and so on. They influence patients’ choice of hospitals to varying degrees [ 38 , 39 , 40 ], according to the research results, “level of physician diagnosis and treatment”, “severe condition of disease”, and “advanced level of medical equipment and technology”. To ensure that “acute and chronic diseases are treated by different facilities” (a goal of the hierarchical medical policy), the municipal government of Beijing needs to strengthen policy publicity and improve infrastructure and service quality in primary hospitals and basic healthcare centers.…”
Section: Discussionmentioning
confidence: 99%